2019
DOI: 10.1111/add.14571
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of nicotine vaping products used by participants in the 2016 ITC Four Country Smoking and Vaping Survey

Abstract: Background and Aims The regulatory environment for nicotine vaping products (NVPs) varies widely across countries and this will probably affect the devices used, nicotine content and usage, and hence the ability of NVPs to substitute for cigarettes. We aimed to describe the types of NVPs used by current vapers in four countries with varying regulatory and enforcement approaches toward the marketing and sale of NVPs. Methods Data are from wave 1 (July-November 2016) of the ITC Four Country Smoking and Vaping Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…14 Vaporized nicotine products have been shown to differ in nicotine delivery, 15−17 reduction of nicotine withdrawal symptoms, 18 and type of VNP used differs between daily and non-daily users. 19 A recent study showed that over one year, 87.0% of smokers did not use a VNP, 6.9% of smokers became experimental VNP users, and only 2.6% became daily VNP users. 20 This study also found that cigarette smokers who became daily VNP users were about 8 times more likely than non-users to self-report 30-day cigarette cessation.…”
Section: Introductionmentioning
confidence: 99%
“…14 Vaporized nicotine products have been shown to differ in nicotine delivery, 15−17 reduction of nicotine withdrawal symptoms, 18 and type of VNP used differs between daily and non-daily users. 19 A recent study showed that over one year, 87.0% of smokers did not use a VNP, 6.9% of smokers became experimental VNP users, and only 2.6% became daily VNP users. 20 This study also found that cigarette smokers who became daily VNP users were about 8 times more likely than non-users to self-report 30-day cigarette cessation.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine vaping products (NVPs), sometimes called electronic cigarettes, are products designed to deliver nicotine without tobacco smoke by heating solutions containing distilled nicotine to create an aerosol (colloquially called ‘vapour’) . NVPs should be distinguished from heated tobacco products which create an aerosol by heating volatile chemicals in tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, approximately one‐third of smokers in Australia (31%) had tried vaping and 4.4% reported currently vaping . It is unclear what proportion of those respondents vape with nicotine, but in a separate study conducted in 2016, 91% of NVP users in Australia reported that their devices contained nicotine . The public′s understanding of the regulations, and their beliefs on what future regulatory frameworks should look like, could inform regulatory efforts and implementation of new NVP‐related policies.…”
Section: Introductionmentioning
confidence: 99%